1981
DOI: 10.1161/01.cir.64.6.1174
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-density lipoprotein and cholesterol-rich very low density lipoprotein in angiographically determined coronary artery disease.

Abstract: The relationship between the concentrations of intermediate-density lipoprotein (IDL) and other lipoproteins and the extent of coronary artery disease (CAD) was studied in 182 consecutive patients evaluated by selective coronary cineangiography. On univariate analysis, the extent of CAD correlated significantly and positively with very low density lipoprotein (VLDL) cholesterol, IDL cholesterol and low-density lipoprotein (LDL) cholesterol, and negatively with high-density lipoprotein (HDL) cholesterol. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1
2

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(84 citation statements)
references
References 46 publications
3
74
1
2
Order By: Relevance
“…However, the interest has been, in general, limited to plasma VLDL concentrations without paying too much attention to the lipoprotein composition. The latter has become increasingly important once the evidence has been forwarded that abnormalities of VLDL composition might be related to the process of atherogenesis [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the interest has been, in general, limited to plasma VLDL concentrations without paying too much attention to the lipoprotein composition. The latter has become increasingly important once the evidence has been forwarded that abnormalities of VLDL composition might be related to the process of atherogenesis [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cholesterol rich VLDL lipoproteins have been shown to contribute to the process of atherosclerosis [6,7]. Therefore, we have undertaken this study in order to evaluate the plasma lipoprotein composition in a group of normolipidaemic young male Type 1 diabetic patients.…”
mentioning
confidence: 99%
“…On univariate analysis the strongest correlations were found between IDL and LDL triglyceride (IDL cholesterol and apolipoprotein B were also significantly related), suggesting that IDL and triglyceride-rich LDL may have the highest "atherogenic potential," as reported in the previously mentioned Japanese study. 8 Nevertheless, in terms of predictive power, plasma triglyceride was found to account for more variability in the score for severity of atherosclerosis than did concentrations of IDL or LDL triglyceride.…”
Section: ±11mentioning
confidence: 95%
“…Similar findings have been reported from Japan where, in one study, increased concentrations of triglyceride (and reduced HDL cholesterol) were found to be stronger predictors of CAD than the plasma cholesterol concentration.30 Another study from Japan demonstrated the significance of IDL and VLDL cholesterol as indicators of severity of coronary atherosclerosis. 8 The severity of coronary atherosclerosis determined at autopsy has also been shown to correlate better with the antemortem plasma concentration of triglyceride than of cholesterol. '1 Atherosclerosis in the large arteries of the legs is generally associated with hypertriglyceridemia.32 In our previous study,5 conducted in a manner similar to the present investigation, LDL triglyceride was one of the three independent predictors of severity score.…”
Section: ±11mentioning
confidence: 99%
“…IDL levels have also been found to be strong predictors of atherosclerosis in genetically hyperlipidaemic [33] and cholesterol-or casein-fed rabbits [34]. In humans without major genetic or secondary forms of hyperlipidaemia, IDL and small VLDL have been shown to be independent predictors of the presence, severity, or progression of atherosclerosis [35][36][37][38][39]. Patients with type III hyperlipoproteinaemia [8], chronic renal failure [40] or NIDDM [41] have elevated levels of remnant lipoproteins as well as accelerated development of atherosclerosis.…”
Section: U Rmentioning
confidence: 98%